Evaluating the timing of former glacier expansions in the Tian Shan: A key step towards robust spatial correlations. (1st December 2016) - Blomdin, R.; Stroeven, A.P.; Harbor, J.M.; Lifton, N.A.; Heyman, J.; Gribenski, N.; Petrakov, D.A.; Caffee, M.W.; Ivanov, M.N.; Hättestrand, C.; Rogozhina, I.; Usubaliev, R.
Abstract: The timing of past glaciation across the Tian Shan provides a proxy for past climate change in this critical area. Correlating glacial stages across the region is difficult but cosmogenic exposure ages have considerable potential. A drawback is the large observed scatter in 10 Be surface exposure data. To quantify the robustness of the dating, we compile, recalculate, and perform statistical analyses on sets of 10 Be surface exposure ages from 25 moraines, consisting of 114 new and previously published ages. We assess boulder age scatter by dividing boulder groups into quality classes and rejecting boulder groups of poor quality. This allows us to distinguish and correlate robustly dated glacier limits, resulting in a more conservative chronology than advanced in previous publications. Our analysis shows that only one regional glacial stage can be reliably correlated across the Tian Shan, with glacier expansions occurring between 15 and 28 ka during marine oxygen isotope stage (MIS) 2. However, there are examples of older more extensive indicators of glacial stages between MIS 3 and MIS 6. Paleoglacier extent during MIS 2 was mainly restricted to valley glaciation. Local deviations occur: in the central Kyrgyz Tian Shan paleoglaciers were more extensive and we propose that the topographic context explains this pattern. Correlation between glacial stages prior to late MIS 2 is less reliable, because of the low number of samples and/or the poor resolution of the dating. With the current resolution and spatial coverage of robustly-dated glacier limits we advise that paleoclimatic implications for the Tian Shan glacial chronology beyond MIS 2 are speculative and that continued work toward robust glacial chronologies is needed to resolve questions regarding drivers of past glaciation in the Tian Shan and Central Asia. Graphical abstract: Highlights: We contribute to and evaluate the timing of glacier expansions in the Tian Shan. We introduce a systematic approach to correlate glacial chronologies. We observe large scatter in 10 Be surface exposure age. We identify only one glacial stage of regional significance 15–28 ka during MIS 2. Correlation of glacial stages prior to MIS 2 is less reliable.